Statistic analysis of 6891 cancer-paining patients＇ information from Gansu Province Tumour Hospital, China - Jin, Yuzhong; Chai, Yandong; Yang, Hua (The Chinese-German journal of clinical oncology, 2009)
Objective： To analyze and gain the interlinking degree of the cancer pain with patients＇ cancer-species, sexuality and age etc. Methods： The information of narcotic drugs used for cancer pain patients in our hospital （Gansu Province Turnout Hospital, China） during 2002-2007 were typed in designed EXCEL form, then counted and analyzed. Results： The total number of cancer pain patients used narcotic drugs during 2002-2007 was 6891 （n = 6891 ）, among them, 4164 （60.44%） were males, and 2727 （39.56%） females. The top-range of cancer-species in those patients was as follows： lung cancer （20.39%）, gastric cancer （14.85%）, esophageal cancer （9.71%）, hysterocarcinoma （6.79%）, liver cancer （6.70%） and breast cancer （6.31%）. Conclusion： （a） The male number of cancer pain patients using narcotic drugs is higher than the female number （1.53：1）. （b） In the cases of lung cancer, gastric cancer, esophageal cancer, liver cancer and kidney cancer, the male numbers are twice more than the female numbers, and the difference between the two groups are significant. （c） Most of the cancer pain patients （over 87%） are over 40 years old.